2018
DOI: 10.1016/j.cortex.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Biased temporal order judgments in chronic neglect influenced by trunk position

Abstract: Numerous studies have reported that temporal order perception is biased in neurological patients with extinction and neglect. These individuals tend to perceive two objectively simultaneous stimuli as occurring asynchronously, with the ipsilesional item being perceived as appearing prior to the contralesional item. Likewise, they report that two stimuli occurred simultaneously in situations where the contralesional item is presented substantially prior to the ipsilesional item. Therefore, they exhibit a biased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The majority of the studies described this subtype as egocentric (viewer-centered) neglect ( n = 11), with some additionally describing that contralesional stimuli from a body centered/egocentric viewpoint are neglected ( 40 , 55 , 95 , 96 ). Some descriptions reported the contralesional side of the spatial environment is neglected ( 97 , 98 ), while others reported the contralesional side of the body is neglected ( 99 , 100 ) or the “boundaries of the neglected space are not constant” ( 101 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies described this subtype as egocentric (viewer-centered) neglect ( n = 11), with some additionally describing that contralesional stimuli from a body centered/egocentric viewpoint are neglected ( 40 , 55 , 95 , 96 ). Some descriptions reported the contralesional side of the spatial environment is neglected ( 97 , 98 ), while others reported the contralesional side of the body is neglected ( 99 , 100 ) or the “boundaries of the neglected space are not constant” ( 101 ).…”
Section: Resultsmentioning
confidence: 99%
“…(3) Allocentric neglect is associated with egocentric neglect. It has been suggested that allocentric deficits are only observed in combination with egocentric neglect ( 97 ), or that the severity of allocentric deficits are influenced by egocentric factors (allocentric deficits are more severe toward the contralesional side) ( 95 , 100 , 105 ). Allocentric neglect has been challenged as a legitimate subtype of neglect, suggesting it is a particular form of egocentric neglect with the attentional window restricted to the individual object/stimuli ( 53 , 103 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to appropriately integrate information from eye, head, and trunk positions to define an egocentric reference frame [20][21][22][23][24][25]. Both hemispheres encode this information from the contralateral space and interact with each other to maintain balance [26].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of right brain damage, an interhemispheric imbalance leads to a rightward deviation of the egocentric space reference, thus resulting in difficulty with a visual search of the left space [24,25]. It has been reported that the head-on-trunk position is related to not only endogenous visual search but also reaction time for stimuli that appear in the neglected space [23]. Rorden et al [23] investigated the relationship between trunk position and stimulus-driven attention.…”
Section: Introductionmentioning
confidence: 99%
“…More details on the distribution of the 72 trials (in the two blocks) on the conditions of the within-subject independent variables are reported in Table 2: The exposure time (ET) of the visual and auditory stimuli was chosen based on previous work, in which time intervals similar to the ones we used were manipulated and shown to reflect short and long durations, respectively, in the cognitive processing of material presented on the specific modality (visual and auditory) (for more details, see [11][12][13].…”
mentioning
confidence: 99%